KONSELING INTENSIF DAPAT MENINGKATKAN EFIKASI DIRI IBU HAMIL DENGAN HEPATITIS B DALAM MENGHADAPI PERSALINAN - Rusyanti, Siti; Rokayah, Yayah; Yuningsih, Nani; Kuswandi, Kadar (Jurnal Medikes (Media Informasi Kesehatan), 2022)
Pregnant women with Hepatitis B must have confidence in their abilities to organize the actions needed to manage the situation during childbirth. Achieving self-efficacy in pregnant women requires internal and external support intensive counselling as part of the management of pregnant women with Hepatitis B. The formulation of the problem in this study is how the description of the self-efficacy of pregnant women with Hepatitis B in dealing with childbirth and whether there is an effect of Intensive counselling on the self-efficacy of pregnant women with Hepatitis B in facing a delivery. The purpose of this study was to describe the self-efficacy of pregnant women with Hepatitis B in dealing with delivery and to determine the effect of intensive counselling on the self-efficacy of pregnant women in dealing with the delivery in Lebak Regency in 2021. This study used a quasi-experimental approach with a pretest-posttest design approach. The sample size in this study was based on the number of pregnant women with Hepatitis B in the Lebak district in July 2021, as many as 32 (Consecutive sampling). Inclusion criteria in this study were pregnant women in the third trimester who suffered from Hepatitis B. Univariate data analysis aimed to present an overview of the frequency distribution of each variable, and bivariate analysis to analyze the relationship between independent and dependent variables, with the non-parametric Wilcoxon test. The results showed an increase in the self-efficacy of pregnant women with Hepatitis B in facing delivery, after intensive counselling, with a value of p = 0.000 (p < ). Pregnant women with Hepatitis B need intensive counselling as external support in preparing for childbirth and caring for their babies. One strategy to increase people’s knowledge and attitudes is through intensive counselling. The provision of health education, including the implementation of counselling, aims to improve knowledge, change behaviour, prevent complications, support health conditions, empowerment and self-efficacy.